Nitrogen fertilizer use efficiency, recovery and leaching of an alexandergrass pasture - Sartor,Laércio Ricardo (2011)
Nitrogen usually determines the productive potential of forage crops, although it is highly unstable in the environment. Studies on recovery rates and use efficiency are important for more reliable fertilizer recommendations to reduce costs and avoid environmental pollution. The purpose of this study was to evaluate N use efficiency and recovery rate of Alexandergrass pasture (Brachiaria - Syn. Urochloa plantaginea) as well as N-NO3- and N-NH4+ soil concentrations using different levels of N fertilization under two grazing intensities. The experiment was arranged in a randomized block design in a factorial scheme with three replications. Treatments consisted of three N rates (0, 200 and 400 kg ha-1 N) and two grazing intensities termed low mass (LM; forage mass of 2,000 kg ha-1 of DM) and high mass (HM; forage mass of 3,600 kg ha-1 of DM) under continuous stocking and variable stocking rates. Results of N fertilization with 200 kg ha-1 were better than with 400 kg ha-1 N. There was a significant effect of N rates on soil N-NO3-concentration with higher levels in the first layer of the soil profile in the treatment with 400 kg ha-1 N. Grazing intensity also affected soil N-NO3- concentration, by increasing the levels under the higher stocking rate (lower forage mass).